Effectiveness and Contribution of Hotel Tax and Restaurant Tax on Regional Original Income at Bapenda Surabaya City - Sonia Agustin; Ec. Sari Andayani (Universitas Muhammadiyah Makassar, 2022)
Regional development will be used to develop the potential and increase the efficiency of the entire financial system for development based on the level of independence of the region. Hotel and Restaurant Tax is a tax that has huge potential in the city of Surabaya. This study aims to analyze and determine the effectiveness and contribution of hotel and restaurant taxes to the Regional Original Income of the City of Surabaya in the period 2016 to 2020. The data collection techniques are documentation and interviews, with effectiveness ratio analysis and contribution analysis. The results of the study prove that (1) the effectiveness of hotel tax revenue and restaurant tax from 2016 to 2019 is more than 100%, while in 2020 it is 60% - 80% and (2) the contribution plays a major role in regional original income with a calculation of 3.60% to 80%. above 5%.